Behavioral self-control - Hester, Reid (Boston, MA : Allyn and Bacon, 2002)
In this tape, Dr. Reid Hester trains a group of participants in behavioral self-control, a set of techniques that can be to eliminate negative behaviors or increase positive habits. People who practice this skill can change their substance use behaviors
Editor, Virginia Lanigan
Moderator: John Carlson, Judy Lewis
Keywords: Self-control; Behavior modification